2011
DOI: 10.1016/j.neulet.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paliperidone and risperidone on extracellular glutamate in the prefrontal cortex of rats exposed to prenatal immune activation or MK-801

Abstract: The NMDA glutamate hypofunction model of schizophrenia is based in part upon acute effects of NMDA receptor blockade in humans and rodents. Several laboratories have reported glutamate system abnormalities following prenatal exposure to immune challenge, a known environmental risk factor for schizophrenia. Here we report indices of NMDA glutamate receptor hypofunction following prenatal immune activation, as well as the effects of treatment during periadolescence with the atypical antipsychotic medications ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…Typical and atypical antipsychotics Impaired cognitive performance Chronic administration of clozapine improved cognitive performance in mice exposed to Poly(I:C)-induced MIA Schizophrenia Clozapine Atypical antipsychotic Impairment in working memory and reduction in hippocampal neurogenesis Chronic administration of clozapine reversed impairments in working memory of mice exposed to Poly(I:C)-induced MIA, no rescue of hippocampal neurogenesis Schizophrenia Piontkewitz et al, 2009 Clozapine Atypical antipsychotic Structural pathologies including enlarged lateral ventricles and reduced hippocampal volumes, as well as behavioral abnormalities relevant to schizophrenia Administration of clozapine during peri-adolescence prevented emergence of behavioral abnormalities and structural brain alterations in adulthood in mice exposed to Poly(I:C)-induced MIA Schizophrenia Roenker et al, 2011 Risperidone, paliperidone…”
Section: The Polyinosinic:polycytidylic Acid Model In Comparison To Omentioning
confidence: 99%
See 1 more Smart Citation
“…Typical and atypical antipsychotics Impaired cognitive performance Chronic administration of clozapine improved cognitive performance in mice exposed to Poly(I:C)-induced MIA Schizophrenia Clozapine Atypical antipsychotic Impairment in working memory and reduction in hippocampal neurogenesis Chronic administration of clozapine reversed impairments in working memory of mice exposed to Poly(I:C)-induced MIA, no rescue of hippocampal neurogenesis Schizophrenia Piontkewitz et al, 2009 Clozapine Atypical antipsychotic Structural pathologies including enlarged lateral ventricles and reduced hippocampal volumes, as well as behavioral abnormalities relevant to schizophrenia Administration of clozapine during peri-adolescence prevented emergence of behavioral abnormalities and structural brain alterations in adulthood in mice exposed to Poly(I:C)-induced MIA Schizophrenia Roenker et al, 2011 Risperidone, paliperidone…”
Section: The Polyinosinic:polycytidylic Acid Model In Comparison To Omentioning
confidence: 99%
“…Along these lines, NMDA glutamate receptor hypofunction, which was effectively blocked by low dose treatment with paliperidone or risperidone, has been proposed as an early developmental consequence of prenatal Poly(I:C) exposure. Hence, the Poly(I:C) MIA model may serve as a tool for the identification of early therapeutic interventions directed at the glutamatergic system, which is known to also be involved in the manifestation of positive and negative symptoms in patients suffering from schizophrenia (Roenker et al, 2011). Supporting the role of NMDA receptors in the mechanistic underpinnings of pharmacotherapy, hippocampal slices of offspring from Poly(I:C) MIA show NMDA/glutamatergic receptor activity specifically related to clozapine and not to haloperidol (Wittmann et al, 2005).…”
Section: Polyinosinic:polycytidylic Acid-assisted Maternal Immune Actmentioning
confidence: 99%
“…1) [12]. It has been reported in an animal model of schizophrenia that after administration of MK-801, the extracellular glutamate concentration was increased in the PFC and that the concentration was normalized after treatment with risperidone or paliperidone; that is after the treatment with D2 and 5-HT2A antagonists [27].…”
Section: Glutamatementioning
confidence: 99%
“…However, the same rats showed a blunted response to MK801-induced increases in extracellular glutamate in the PFC (Roenker et al 2011). This study suggests that glutamatergic neurotransmission might have been suppressed at least proximal to adolescent APD exposure.…”
Section: Neurochemical Effects Proximal To Adolescent Apd Administrationmentioning
confidence: 92%
“…This altered glutamate level was prevented by adolescent treatment with risperidone or paliperidone (both at 0.01 mg/kg/day from PND35 to PND56) (Roenker et al 2011). The same group has reported that amphetamine-induced locomotor abnormalities at PND91-92 in Poly I:C rats can be ameliorated by adolescent treatment with risperidone or paliperidone or aripiprazole (Richtand et al 2012).…”
Section: Maternal Immune Activation Models (Mia)mentioning
confidence: 93%